The Influence of e-Servqual toward e-Word of Mouth through e-Customer Satisfaction and e-Customer Trust in e-Commerce Apparel in Surabaya - Gunawan, Hery; Susanti, Christina Esti (Technium Social Sciences Journal, 2021)
The purpose of this research is to analyze the transformation of customer behavior from conventional to digital, where services, nowadays, have been systematically integrated into a website or an application. e-commerce, which is a new business power, has transformed into a place for the customers to exchange information through any words that massively influence the customers’ satisfaction and trust. In this research, there was also an observation about how e-commerce is able to maintain its business in the era of 4.0, where the competition has been tighter. This research is a causal research which used the primer data and the likert scale to measure the answers of the respondents. The method of the data collection used the questionnaires which were distributed to 200 respondents, while the technique of the data analysis used the Structural Equation Modeling (SEM). The results of this research proved that the good service quality could increase the customers’ satisfaction and trust, but the good service quality failed to encourage the customers to exchange information through the online media. Moreover, the results of this research also proved that the customers who had trust would exchange information, but the customers who felt satisfied were not willing to exchange information. Simultaneously, the good service quality, the customers’ satisfaction and trust failed to encourage the customers to exchange information in an e-commerce website or application. Based on the results of this research, the e-commerce providers should always give honest services to the customers because that will encourage the customers to be involved in the development of e-commerce through stories, recommendations and responses which are given in online media through a website or an application.